2004
DOI: 10.1002/pros.20003
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of bioluminescent LNCaP‐luc‐M6 Tumors: A new animal model for the study of metastatic human prostate cancer

Abstract: The LNCaP-luc-M6 cell line is a bioluminescent, hormone-sensitive prostate cancer cell line applicable for BLI studies to non-invasively monitor subcutaneous and orthotopic prostate tumor growth and metastasis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 34 publications
1
48
2
Order By: Relevance
“…The establishment and growth of tumors were monitored by bioluminescent imaging with the IVIS imaging system (Xenogen Corp., Alameda, CA) according to a protocol similar to those described. [45][46][47][48] Briefly, mice were administered firefly luciferin through intraperitoneal injection (100 L/mouse). Approximately 5 minutes later, while under isoflurane anesthesia, mice were imaged with a highly sensitive, cooled charged-coupled device camera in the light-tight specimen chamber of the IVIS system.…”
Section: Reagentsmentioning
confidence: 99%
“…The establishment and growth of tumors were monitored by bioluminescent imaging with the IVIS imaging system (Xenogen Corp., Alameda, CA) according to a protocol similar to those described. [45][46][47][48] Briefly, mice were administered firefly luciferin through intraperitoneal injection (100 L/mouse). Approximately 5 minutes later, while under isoflurane anesthesia, mice were imaged with a highly sensitive, cooled charged-coupled device camera in the light-tight specimen chamber of the IVIS system.…”
Section: Reagentsmentioning
confidence: 99%
“…Inefficient cell uptake of D-luciferin due to alterations in tumour blood supply and cell membrane permeability decreases the luciferase activity. Scatena et al [43] also observed constant bioluminescent signals in prostate tumours despite the 3.3-fold increase in tumour volume. This indicates that luciferase expression can be lost in time, probably owing to genomic instability.…”
Section: Discussionmentioning
confidence: 88%
“…Docetaxel (Taxotere, Henry Schein) was prepared according to the manufacturer's instructions. Luciferaseexpressing COLO205 cells were stably transfected to constitutively express luciferase (28 ; 2577, dilution 1:200) were ordered from Cell Signaling. Anti-Chk1 antibody was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, G-4).…”
Section: Methodsmentioning
confidence: 99%